341. Clinical and Laboratory Data in Patients with Viral and Bacterial Meningitis in Conjunction with FilmArray Meningitis/Encephalitis Panel Use: A Multi-Site Retrospective Cohort Study. (31st December 2020) - Goodrich, Nathaniel; Nabower, Aleisha M; Rajbhandari, Prabi; Martin, Kimberly C; Ekambaram, Maheswari; Eisenberg, Jaclyn; McCulloh, Russell; Cipriano, Frank; Stone, Bryan; Lyden, Elizabeth; Snowden, Jessica
Abstract: Background: The ability to quickly recognize and diagnose meningitis is a critical component in its management. The use of the FilmArray Meningitis/Encephalitis (ME) panel has made pathogen identification easier and faster. Although literature exists regarding clinical and laboratory data in patients with bacterial meningitis, less is known about the characteristics of viral meningitis caused by viruses detected by the ME panel This study aims to compare differences in clinical and laboratory characteristics between viral and bacterial meningitis identified by the ME panel. Methods: We conducted a multisite retrospective review of pediatric patients with cerebral spinal fluid (CSF) positive for viral or bacterial organisms from January 2015 - February 2019. Demographic, clinical, and lab characteristics were extracted from medical records. Frequencies and percentages are used to explain descriptive data. Fisher's exact test was used for categorical data. The Mann-Whitney test was used for continuous data. Results: Four hundred thirty-eight patients were included in the analysis with baseline characteristics found in Table 1. Among these, 345 and 93 patients tested positive for viral and bacterial organisms respectively. Viral organisms identified are presented in Figure 1. Patients with bacterial organisms were more likely to have a history of prematurity, a prior neurosurgical procedure, neurological symptoms at presentation, neurological complications, and death within 30 days of admission. The median serum white blood cell (WBC) count, C-reactive protein (CRP), procalcitonin, CSF WBC count, CSF neutrophil percentage, and CSF protein were significantly higher in patients with bacterial organisms compared to viral organisms (Table 2). Table 1: Baseline Characteristics of the Study Population Figure 1: Viral organisms identified. Table 2: Comparison of Laboratory Data by CSF Pathogen Group Conclusion: Patients positive for bacterial meningitis were more likely to have higher markers of infection compared to patients with viral organisms. Patients with bacterial organisms were also more likely to have death within 30 days of admission and neurological symptoms and subsequent complications, although the small number of patients limits these conclusions. These findings may help clinicians utilize clinical and laboratory data in conjunction with a ME panel result. Disclosures: All Authors : No reported disclosures